Radiomics and dosiomics for predicting radiation-induced hypothyroidism and guiding intensity-modulated radiotherapy - Yang, Shan-Shan; Peng, Qing-He; Wu, Ai-Qian; Zhang, Bao-Yu; Liu, Zhi-Qiao; Chen, En-Ni; Xie, Fang-Yun; OuYang, Pu-Yun; Chen, Chun-Yan (iScience, 2023)
To guide individualized intensity-modulated radiotherapy (IMRT), we developed and prospectively validated a multiview radiomics risk model for predicting radiation-induced hypothyroidism in patients with nasopharyngeal carcinoma. And simulated radiotherapy plans with same dose-volume-histogram (DVH) but different dose distributions were redesigned to explore the clinical application of the multiview radiomics risk model. The radiomics and dosiomics were built based on selected radiomics and dosiomics features from planning computed tomography and dose distribution, respectively. The multiview radiomics risk model that integrated radiomics, dosiomics, DVH parameters, and clinical factors had better performance than traditional normal tissue complication probability models. And multiview radiomics risk model could identify differences of patient hypothyroidism-free survival that cannot be stratified by traditional models. Besides, two redesigned simulated plans further verified the clinical application and advantage of the multiview radiomics risk model. The multiview radiomics risk model was a promising method to predict radiation-induced hypothyroidism and guide individualized IMRT. [Display omitted] •The multiview radiomics risk model can predict radiation-induced hypothyroidism•The multiview radiomics risk model performed better than the NTCP model•The multiview radiomics risk model can guide intensity-modulated radiotherapy Radiology; Radiological technology; Assessment in health technology